The Effect of 8 Weeks of Rotator Cuff Muscle Specific Exercises on the Range of Motion, Strength, and Electrical Activity of Selected Shoulder Muscles in Man Volleyball Players with Glenohumeral Internal Rotation Deficit - Mohsen Moradi; Maliheh Hadadnezhad; Amir Letafatkar (Vesnu Publications, 2019)
Introduction: Disorder and injury in the shoulder joint have a high prevalence in overhead throwing athletes such as volleyball players. The glenohumeral internal rotation deficit is directly related to shoulder injuries. Therefore, the purpose of this study was to assess the effect of 8 weeks of rotator cuff muscle specific exercises on the range of motion, strength, and electrical activity of selected shoulder muscles in man volleyball players with shoulder internal rotation deficit. Materials and Methods: Thirty man athletes with glenohumeral internal rotation deficit participated in this study. After initial screening and identifying qualified athletes, the subjects were divided into equal groups of experimental and control. Specific rotator cuff exercises included stretching, strength, neuromuscular, and performance exercises. The range of motion was measured with goniometer, strength with isokinetic device, and electrical activity of the muscles with electromyographic device. Results: Specific exercises of rotator cuff muscles improved muscle strength in concentric and eccentric contractions (P < 0.001), decreased supraspinatus (P = 0.001), infraspinatus (P = 0.001), anterior deltoid (P = 0.005), and posterior deltoid (P = 0.004) muscle activity, and increased internal rotaion range of motion of shoulder joint (P < 0.001). Conclusion: According to positive influence of specific rotator cuff exercises on the range of motion, strength, and electrical activity of selected shoulder muscles, adding these programs to the volleyball rehabilitation therapy programs of athletes with an glenohumeral internal rotation deficit is recommended to improve the limitations of injury.